The impact of tourism development on islamic religious behavior in ngadiharjo village, borobudur district - Fouad Larhzizar; Zidna Nabila ‘Ainun Nadzif; Triana Hermawati (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aims to analyze the impact of tourist attractions on the religious behavior of the community in Ngadiharjo Village, Borobudur District. The increasing development of tourism in the area has brought diverse external influences through incoming visitors, potentially shifting local religious practices. Using a phenomenological approach within Islamic studies, this qualitative field research collected data through interviews with religious leaders, community figures, and local residents, supported by observation and documentation. The findings reveal both positive and negative impacts. On the positive side, tourism has encouraged the revival of Islamic-based traditions, such as the merti desa ritual, and improved economic conditions by creating jobs and reducing unemployment. On the negative side, exposure to tourists has led to behavioral shifts that conflict with Islamic values, including changes in dress and lifestyle influenced by Western norms. Contributing factors include an increasingly open mindset among locals, environmental influences from tourist interactions, and broader socio-cultural changes driven by infrastructure development.